Necesidad de que los niños y niñas comprendidos en la edad de nueve a doce años sean escuchados dentro de las audiencias que se desarrollan para determinar el régimen de visitas, garantizando su participación y cumpliendo con el principio constitucional de desarrollo integral - Cabrera Loayza, Emily Karelys (2022)
The present research work is carried out in view of the evident need for children between the ages of nine and twelve to participate in the development of hearings for the establishment or regulation of the visitation regime, in order to guarantee the fulfillment of their rights and constitutional principles, which in this case would be the right to be heard, the right to participate, to have an optimal integral development, to be consulted, to enjoy family coexistence, to a dignified life and that the best interest of the child prevails to the fullest. Currently, the hearings for the establishment of the visitation regime are held before a Judge of the Family, Women, Children and Adolescents with the intervention of both parents and their advocates, likewise, the Organic Code of Children and Adolescents establishes that children under twelve years of age may participate but the judge will value their opinion according to their age and maturity, which I consider erroneous since based on the studies of doctrinarians and professionals in psychology determine that a child begins his or her stage of conscience and logic from 7 to 9 years of age, so that, from this age they already have a formed criterion and are in the capacity to provide an optimal opinion which protects their interests, which is why it is considered necessary for the judge to listen and take into account the participation of the minor before resolving. It is important to mention that before the intervention of the minor involved in the hearing, a psychological analysis should be carried out by professionals or social workers and through a report to establish under what circumstances or in what way the minor has been affected by the litigation of their parents, because when there are such disputes the main affected are always children, Once the report is issued by the psychology professionals, if deemed necessary, it should be determined whether the child is able to participate or needs some psychological treatment after a hearing, so that their interests can be safeguarded. Ecuador is a constitutional State of rights and justice which seeks to guarantee compliance with the fundamental and constitutional rights of the Magna Carta, as children are considered a group of priority attention, the main thing before resolving a case where they are affected is to take into account their interests, Despite the fact that the Organic Code for Children and Adolescents aims to provide comprehensive protection where the State, society and the family guarantee all children the enjoyment of their rights with the objective of achieving their integral development based on the constitutional principle of the best interest of the child, this is not fully complied with, This is evidenced within the visitation regime, starting with his family, which violates the enjoyment of a family coexistence and stability in his life, likewise, when the judge resolves without taking into account the participation of the minor, he is not paying attention to his interests or basic needs without knowing the situation he is going through, in this way, not only the rights mentioned above are being violated but also a bad decision would hinder his optimal integral development and his stages of growth and maturity would not be adequate, thus affecting the best interest of the minor.